Eksploitasi Pekerja Perempuan Melalui Modus Staycation dalam Perpanjangan Kontrak Kerja - Sri Fadliati; Sukiati Sukiati (Al-Adalah: Jurnal Hukum dan Politik Islam, 2023)
In industrial relations, staycation used as an instrument by superiors to deceive and force female workers into unsafe and detrimental situations. The promise of a contract extension is an attraction. Female workers who are vulnerable or feel threatened by losing their jobs may be trapped in the practice of staycations with superiors. This study aims to examine the practice of exploitation of female workers through the staycation mode and analyze forms of positive legal protection and Islamic criminal law. This study uses normative legal research methods through a statutory approach and an analytical approach. The results of the study show that practicestaycation as a condition for extending an employment contract is not justified either from a moral or legal aspect. This act can be criminally charged. However, legal proof is difficult, because it requires courage from the victim to report and reveal the incident they experienced. From a positive legal aspect, female workers are protected through labor law, job creation law and sexual violence crime law. From the perspective of Islamic criminal law, this criminal act is included in the judimah hudud. The legal protection offered is in the form of preventive and repressive legal protection. Preventive legal protection in the Qur'an is the prohibition on forcing others and the prohibition on approaching adultery. Meanwhile, repressive protection for adultery perpetrators (if they are married) is stoning to death. Meanwhile, if the perpetrator of adultery (not married) then the punishment or sanction is to be whipped 100 times and exiled for a year. This study helps develop discourse on legal resolution of criminal acts of exploitation of women's labor. Apart from that, it is hoped that this study will help develop discourse on the defense of weak women